X-RAY AND OPTICAL CORRELATION OF TYPE I SEYFERT NGC 3516 STUDIED WITH SUZAKU AND JAPANESE GROUND-BASED TELESCOPES - Noda, Hirofumi; Minezaki, Takeo; Watanabe, Makoto; Kokubo, Mitsuru; Kawaguchi, Kenji; Itoh, Ryosuke; Morihana, Kumiko; Saito, Yoshihiko; Nakao, Hikaru; Imai, Masataka; Moritani, Yuki; Takaki, Katsutoshi; et al. (The Astrophysical journal, 2016)
ABSTRACT From 2013 April to 2014 April, we performed X-ray and optical simultaneous monitoring of the type 1.5 Seyfert galaxy NGC 3516. We employed Suzaku and five Japanese ground-based telescopes-the Pirka, Kiso Schmidt, Nayuta, MITSuME, and the Kanata telescopes. The Suzaku observations were conducted seven times with various intervals ranging from days or weeks to months, with an exposure of ∼50 ks each. The optical B-band observations not only covered those of Suzaku almost simultaneously, but also followed the source as frequently as possible. As a result, NGC 3516 was found in its faint phase with a 2-10 keV flux of 0.21-2.70 × 10−11 erg s−1 cm−2. The 2-45 keV X-ray spectra were composed of a dominant variable hard power-law (PL) continuum with a photon index of ∼1.7 and a non-relativistic reflection component with a prominent Fe-K emission line. Producing the B-band light curve by differential image photometry, we found that the B-band flux changed by ∼2.7 × 10−11 erg s−1 cm−2, which is comparable to the X-ray variation, and we detected a significant flux correlation between the hard PL component in X-rays and the B-band radiation, for the first time in NGC 3516. By examining their correlation, we found that the X-ray flux preceded that in the B band by days (1 error). Although this result supports the X-ray reprocessing model, the derived lag is too large to be explained by the standard view, which assumes a "lamppost"-type X-ray illuminator located near a standard accretion disk. Our results are better explained by assuming a hot accretion flow and a truncated disk.